Implementación de clústeres: una estrategia para aumentar la competitividad en la industria floricultura colombiana 2000-2018 (2021)
Business areas have implemented strategies such as the use of clusters as an alternative to increase the competitiveness of countries and between them the global floriculture industry and the main exporter of the same as the Netherlands. This work seeks to determine the effects of cluster implementation on the Colombian floriculture industry because of the tradition I have importance that it has within the country and that it is currently lagging behind, therefore an analysis was carried out through the comparison between Colombia and the Netherlands; for this comparison, market share, production and exports were taken into account by identifying the advantages and/or contributions of the European country through the aforementioned implementation, and from the methodology of Porter diamond and its five competitive forces define the effects of implementation on Colombian floriculture.